The clustering and evolution of H-alpha emitters at z~1 from HiZELS - Sobral, D; Best, P; Geach, J; Smail, I; Cirasuolo, M; Garn, T; Dalton, G; Kurk, J (2009)
(Abridged) The clustering properties of a well-defined sample of 734 H-alpha emitters at z=0.84 obtained as part of the Hi-z Emission Line Survey (HiZELS) are investigated. The spatial correlation function is very well-described by (r/r_0)^-1.8, with r_0=2.7+-0.3Mpc/h. The correlation length r_0 increases strongly with H-alpha luminosity, L_H-alpha, from r_0~2Mpc/h for the most quiescent galaxies (star-formation rates of ~4M_sun/yr), up to r_0>5Mpc/h for the brightest galaxies in H-alpha. The correlation length also increases with increasing rest-frame K-band luminosity (M_K), but the r_0-L_H-alpha correlation maintains its full statistical significance at fixed M_K. At z=0.84, star-forming galaxies classified as irregulars or mergers are much more clustered than discs and non-mergers, but once the samples are matched in L_H-alpha and M_K, the differences vanish, implying that the clustering is independent of morphological type at z~1. The typical H-alpha emitters found at z=0.84 reside in dark-matter haloes of ~10^12M_sun, but those with the highest SFRs reside in more massive haloes of ~10^13M_sun. Comparing the results with those of H-alpha surveys at different redshifts, it is seen that although the break of the H-alpha luminosity function, L*, evolves by a factor of ~30 from z=0.24 to z=2.23, galaxies with the same L_H-alpha/L*(z) are found in dark matter haloes of similar masses, independently of cosmic time. This not only confirms that star-formation is more efficient at higher redshift, but also suggests a fundamental connection between the strong decrease of L* since z=2.23 and the quenching of star-formation in galaxies residing within dark-matter haloes significantly more massive than 10^12M_sun at any given epoch.